Temporal glioblastoma presenting as catatonia. Issue 3 (4th March 2019) - Franssen, Anouchka; Sienaert, Pascal
Abstract : The objective of this article is to describe the possible association of catatonia and temporal brain lesions. This is a case presentation of a 57-year-old man presenting with depression, with catatonia secondary to a temporal glioblastoma. He was referred to hospital because for a sudden deterioration in depressed state. He was diagnosed with catatonia and treated successfully with lorazepam. During his admission, he became increasingly disinhibited, and an MRI scan revealed an intracranial mass in the right temporal lobe, with uncal herniation and a mass effect. Surgical resection of the entire tumour was successful. Histological examination revealed a glioblastoma multiforme requiring additional chemoradiotherapy. Postoperatively, catatonic signs and symptoms were not detectable. A postsurgical frontal syndrome with disinhibition and logorrhoea was present and gradually normalised over the course of several weeks. Catatonia can be the presenting symptom of a temporal brain tumour, and should therefore prompt the physician to a thorough medical investigation.